Eco-Friendly Extraction of Sinapine From Residues of Mustard Production - Flourat, Amandine L.; Willig, Gaëlle; Teixeira, Andreia R. S.; Allais, Florent (Frontiers in Sustainable Food Systems, 2019)
In this study, our efforts were focused on the optimization of phenolic compounds - mainly sinapine - extraction from residues of industrial mustard production. A preliminary work was conducted to discuss the way data from Folin-Ciocalteu analytical method are reported and exploited in the literature, and to determine whether methanol can be replaced by ethanol as extracting solvent. As this first question had found a positive answer, an optimization of the extraction process on crude and pretreated industrial residue was achieved using a Response Surface Methodology (RSM). Optimal conditions obtained through this Design of Experiments (DoE) allowed the extraction of more than 10 mg/g of defatted and dried matter (aka DDM) of phenolics from defatted and dried matter, and 13 mg/g DDM of phenolics from non-pretreated matter (results expressed as equivalent of DDM).